Facile fabrication of micropattern surfaces with controlled wettability on PDMS-modified fiber membranes for cell patterning. Issue 18 (28th April 2022) - Xie, Chenchen; Sun, Baishun; Liu, Ri; Qu, Kaige; Zhang, Wenxiao; Weng, Zhankun; Wang, Zuobin
Abstract : The preparation method of modified fiber membranes provides a novel approach to develop cell culture matrices for cell patterning in tissue engineering. Abstract : Various cell culture substrates have been developed for cell patterning to control cell distributions and orientations in tissue engineering, drug screening and regenerative medicine. In this study, a preparation method of modified fiber membranes was applied in the field of cell patterning, and the obtained fiber membranes guided the cell distributions and orientations flexibly. The aligned electrospinning fiber membranes were dip-coated with polydimethylsiloxane (PDMS) to improve the stability of wettability, and then it was treated with oxygen plasma with a photomask to obtain a hydrophilic–hydrophobic surface micropattern. The morphologies, wettabilities and chemical structures of the membranes were analyzed by using a scanning electron microscope (SEM), drop shape analysis instrument, energy dispersive spectrometer (EDS) and Fourier transform infrared (FTIR) spectrometer. The L929 cells were cultured on the obtained membranes to observe the controlled cell distributions and orientations by using a SEM and fluorescence microscope. The results indicate that the treated membranes have the ability to control both cell distributions and orientations simultaneously. This method offers a novel approach to develop cell culture substrates for cell patterning in tissue engineering.